Characterization of Patients with Amyotrophic Lateral Sclerosis attending the Muscular Dystrophy Association–Supported Clinics in Puerto Rico - Deliz, Brenda; Ramos, Kathya; Pérez, Cynthia M. (Puerto Rico Health Sciences Journal, 2018)
Objective: To evaluate the sociodemographic characteristics and clinical and functional profile of amyotrophic lateral sclerosis (ALS) patients evaluated at Puerto Rico’s Muscular Dystrophy Association–supported (MDA) clinics. Methods: A retrospective review of 76 medical records of ALS patients evaluated at any of four MDA-sponsored clinics in Puerto Rico. Results: The mean age of diagnosis was 57.4 ± 11.1 yrs. Most of the patients (52.3%) were women. The majority of the cases were sporadic (48.7%). Over 40% of the patients were diagnosed at one year or earlier. Patients with initial upper extremity involvement (63.2%) were diagnosed earlier (≤ 6 months) than any of the others. The most common presentation of the disease overall was lower extremity weakness (34.2%), which was followed by a bulbar presentation (31.6%). There was a marked difference between men and women in disease presentation, with bulbar involvement in 75% of the women. Conclusion: This study characterized a sample of ALS patients in Puerto Rico who are receiving services at the MDA-sponsored clinics. Puerto Rican patients have similarities with published data from the United States and other countries, including: sporadic pattern, initial symptoms in extremities, and time to diagnosis. Major differences are that the disease was more common in women than in men and that a higher than expected percentage of patients presented with bulbar onset. This may partly account for the overall predominance of the disease in women over men as found in our study, since the bulbar presentation has been reported to be more common in women. Studies with a greater number of patients are needed to determine whether our findings are reproducible. This study will serve as a basis for designing future analytic studies regarding etiology or the factors that might modulate disease progression.